2017
DOI: 10.1007/s00253-017-8625-6
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of E. coli in biomimetic and Fe3O4-doped hydrogel: structural and viability analyses

Abstract: The current study reports the modification of prokaryotic microorganism through a single-layer technique by using different polyanions/cations and doping with magnetic (FeO) nanoparticles. Briefly, individual Escherichia coli cells were encapsulated through deposition of 1% sodium alginate as first layer followed by depositing precipitate layers of calcium chloride, disodium hydrogen phosphate, and FeO nanoparticles. Surface and cross sectional analysis of modified E. coli cells by field emission scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Table 1 shows the zeta-potential of CNC in the suspension with poly (vinyl alcohol) (PVA) with different ratios, which indicated that neat CNC suspension owned an extremely high zeta potential of -72.2 mV. As the PVA percentage increased, the zeta potential decreased but remained at a high level of > 30 mV, which indicated the suspensions were still highly stable (Kiprono et al 2018). In order to eliminate the chiral structure, the zeta potential of the CNC dispersion should not be too high to achieve the uniaxial assembly with higher orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the zeta-potential of CNC in the suspension with poly (vinyl alcohol) (PVA) with different ratios, which indicated that neat CNC suspension owned an extremely high zeta potential of -72.2 mV. As the PVA percentage increased, the zeta potential decreased but remained at a high level of > 30 mV, which indicated the suspensions were still highly stable (Kiprono et al 2018). In order to eliminate the chiral structure, the zeta potential of the CNC dispersion should not be too high to achieve the uniaxial assembly with higher orientation.…”
Section: Resultsmentioning
confidence: 99%
“…polyanions/cations, biopolymers, and magnetic (Fe 3 O 4 ) nanoparticles without compromising their viability [12], thus supporting the development of core-shell hybrid structures and composites. Microbes not only can perform biological functions as individuals, but these also can replicate and be readily distributed and expanded to form functional colonies.…”
Section: Introductionmentioning
confidence: 94%
“…27,28 Magnetic functionalization of cells was also realized by decorating Fe 3 O 4 nanoparticles onto the cell surface by using the polymer-directed strategy. 29,30,129,206,207 PDA was employed as an interlayer for subsequent combination of magnetic iron oxide nanoparticles modified with carboxylic acid. 129 In addition, carbon materials were also coupled with cells under polymer assistance.…”
Section: Polymer-directed Engineering Of Cell-based Biocompositesmentioning
confidence: 99%